1997
DOI: 10.1002/(sici)1097-4644(199705)65:2<172::aid-jcb4>3.3.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of epitope structure of PSP94 (prostate secretory protein of 94 amino acids): (I) immuno‐dominant and immuno‐recessive area

Abstract: PSP94 is a potential biomarker for evaluating patients with prostate carcinoma. We have systematically studied the epitope structure of PSP94 by using a polyclonal antibody against human PSP94. Results of peptide mapping and ELISA tests of dose response to rabbit antiserum against human PSP94 protein showed that only the N-terminal peptides (N30 and M23) are immunoreactive while all the synthetic peptides (C28, C10) located closer to the C-terminus are completely devoid of antigenic activity with the polyclona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Xuan et al (5) have demonstrated a high affinity of PSP94 bound with serum proteins with molecular weight larger than IgG and albumin and have determined that the majority of serum PSP94 is complexed in a bound form. They also noted (7,8) that the N‐terminus of PSP94 is an immunodominant area and is supposed to be exposed outside in the superstructure of natural PSP94. Thus, Wu et al (5) indicated the inability of polyclonal or monoclonal antibodies to recognize the bound PSP94.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Xuan et al (5) have demonstrated a high affinity of PSP94 bound with serum proteins with molecular weight larger than IgG and albumin and have determined that the majority of serum PSP94 is complexed in a bound form. They also noted (7,8) that the N‐terminus of PSP94 is an immunodominant area and is supposed to be exposed outside in the superstructure of natural PSP94. Thus, Wu et al (5) indicated the inability of polyclonal or monoclonal antibodies to recognize the bound PSP94.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant PSP94 (6–8) at a concentration of 0.25 μg/ml was used to coat 96‐well culture plates. The standard dilution of purified IgG plolyclonal rabbit antihuman PSP94 antibody was then prepared from a stock solution of 100 ng/μl.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation